ORGANIZATION OF DISTANCE EDUCATION IN A HIGHER EDUCATIONAL INSTITUTION AS A SOCIO-PEDAGOGICAL PROBLEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the article, the need to organize distance learning in higher education institutions, the importance of using electronic programs and tools in educational institutions. Opinions about the conceptual modern pedagogical rules of distance education are presented.